STAKEHOLDER PRESSURE MODERATES ENVIRONMENTAL, SOCIAL, GOVERNANCE (ESG) DISCLOSURE ON FIRM PERFORMANCE - David Parningotan Gultom; Iin Rosini; Nofryanti (ZILLZELL MEDIA PRIMA, 2024)
This research aims to analyze the impact of Environmental, Social, and Governance (ESG) disclosure on the performance of mining companies, moderated by stakeholder pressure. The research data was obtained from 72 mining companies listed on the Indonesia Stock Exchange (IDX) for the period 2020-2023. The analysis techniques used are panel data regression and moderated panel data regression. The results of the study show that environmental and governance disclosure positively affects the performance of mining companies. This means that the higher the quality of environmental and governance disclosure, the better the company's performance. However, social disclosure does not show a significant effect on company performance. The findings of this study also indicate that stakeholder pressure does not moderate the relationship between Environmental, Social, and Governance (ESG) disclosure and the performance of mining companies. This means that the pressure from stakeholders is not sufficient to strengthen or weaken the relationship between Environmental, Social, and Governance (ESG) disclosure and company performance. The results of this research provide important implications for mining companies, investors, and regulators. For mining companies, it is important to improve the quality of environmental and governance disclosure to enhance company performance. For investors, it is important to consider Environmental, Social, and Governance (ESG) disclosure in investment decision-making. For regulators, it is important to strengthen regulations related to Environmental, Social, and Governance (ESG) disclosure and increase oversight of mining companies.